Uncertainty and International Negotiations on Tradable Quota Treaties - Morten Søberg (Statistics Norway, Research Department, 1998)
Negotiating an international tradable quota treaty between industrialised and developing countries is complicated by uncertain marginal abatement costs and non-uniform quota prices. An initial quota allocation that implies zero expected net cost to developing countries will typically be insufficient to attract their participation in the treaty. Two options to compensate for uncertainty are discussed here, extra emissions quotas and financial transfers. The latter is found to be more effective in facilitating treaty-making, but the scope of co-operation is restricted by the developing countries' risk-aversion.
Keywords: D23; Q25; 330; Tradable quotas; uncertainty